The effects of hydroxycarbamide on the plasma proteome of children with sickle cell anaemia. (29th May 2019) - Brewin, John; Tewari, Sanjay; Menzel, Stephan; Kirkham, Fenella; Inusa, Baba; Renney, George; Ward, Malcolm; Rees, David C.
Summary: We investigated changes in the plasma proteome of children with sickle cell anaemia (SCA) associated with hydroxycarbamide (HC) use, to further characterize the actions of HC. Fifty‐one children with SCA consented to take part in this study. Eighteen were taking HC at a median dose of 22 mg/kg, and 33 were not on HC. Plasma was analysed using an unbiased proteomic approach and a panel of 92 neurological biomarkers. HC was associated with increased haemoglobin (Hb) (89·8 vs. 81·4 g/l, P  = 0·007) and HbF (6·7 vs. 15·3%, P  < 0·001). Seventeen proteins were decreased on HC compared to controls by a factor of <0·77, and six proteins showed >1·3 increased concentration. HC use was associated with reduced haemolysis (lower α, β, δ globin chains, haptoglobin‐related protein, complement C9; higher haemopexin), reduced inflammation (lower α‐1‐acid glycoprotein, CD5 antigen‐like protein, ceruloplasmin, factor XII, immunoglobulins, cysteine‐rich secretory protein 3, vitamin D‐binding protein) and decreased activation of coagulation (lower factor XII, carboxypeptidase B2, platelet basic protein). There was a significant correlation between the increase in HbF% on HC and haemopexin levels ( r  = 0·603, P  = 0·023). This study demonstrated three ways in which HC may be beneficial in SCA, and identified novel proteins that may be useful to monitor therapeutic response.